الاستراتيجية العسكرية الفرنسية في مواجهة ثورة التحرير الجزائرية بالريف حماية المزارع أنموذجا - بن عتو, رضا (University of Eloued جامعة الوادي, 2020)
ملخص: مع تزايد وتيرة حرب التحرير الجزائرية أصبح الريف مسرحا للأحداث، فجيش التحرير الوطني وضع الريف أولوية لتطبيق إستراتيجية حرب العصابات فكانت مزارع الكولون هدفا من أهداف هذه الحرب فيما سوف يصطلح عليه بحرب المزارع، تقوم طبيعة هذه الحرب على استهداف كل ما يمثل نشاطا زراعيا أوروبيا بالجزائر بالحرق والتدمير، حاولت الإدارة الفرنسية مواجهة حرب المزارع بتطبيقها للعديد من الحلول فإلى جانب المشاريع الإغرائية التي منحتها للكولون المزارعين من أجل البقاء في مزارعهم، نجدها تطبق مشاريع عسكرية أخرى هدفها حماية المزرعة من هجمات جيش التحرير الوطني. Abstract: With the increasing pace of the Algerian war of liberation, the countryside became the scene of events. The National Liberation Army placed the countryside as a priority for the implementation of the guerrilla strategy. The colon farms were one of the objectives of this war in what would be called the war of the farms. The nature of this war is to target all the agricultural activity in Europe. Burning and destruction of the most prominent remnants of the farm war on the colon deterioration of the psychological situation, which reflected negatively on their activities due to the deterioration of security in the countryside the French administration tried to confront the farmer's war by applying various solutions. In addition to the projects that it granted to colonists farmers in order to stay in their farms, Military campaign to protect the farm from the attacks of the Liberation Army
مقال
Keywords: الكلمات المفتاحية: الثورة الجزائرية؛ حرب المزارع؛ الريف؛ الحماية؛ الوحدات العسكرية؛ المزرعة النموذجية. ; key words: Algerian Revolution؛ Farm War؛ Rural؛ Protection؛ Military Units؛ Farm pilots.